Edukasi Penanganan Cedera Akut Pada Komunitas Bulutangkis Di Gor Bello, Laweyan : Metode RICE - Totok Budi Santoso; Cikiesa Ilham Faiz; Desvita Savitri Kusuma Wardhani; Novita Sri Wulandari (Universitas 45 Surabaya, 2023)
Badminton is included in the category of non-contact sports which can be played individually or in groups, where the game of badminton requires many combinations of movements such as stepping, jumping, lunges, and quite a bit of acceleration and arm movement. Usually a badminton match from the start of the game to the end takes around 30-90 minutes or more, this shows that badminton is a sport that requires good body condition. Musculoskeletal complaints are a disease caused by repetitive work or unergonomic working methods. Musculoskeletal disorders (MSDs) usually appear as pain in the nerves, muscles or tendons. In Indonesia alone, the prevalence of Musculoskeletal Disorders (MSDs) is 11.9% based on diagnosis by health workers, whereas if seen based on symptoms the prevalence is 24.7%. The aim of this activity is to gain insight into the first treatment for sports injuries in badminton players in Gor Bello, Laweyan. This activity carried out counseling using the lecture method using poster media and evaluation of knowledge of injury management was carried out using a questionnaire both before and after providing the counseling. The conclusion of this community activity is that education regarding handling injuries to badminton players has had a positive impact in increasing knowledge among badminton players at Gor Bello Laweyan regarding handling badminton sports injuries using the RICE method.